2016
DOI: 10.1007/s12594-016-0545-z
|View full text |Cite
|
Sign up to set email alerts
|

Late Eocene-Early Miocene Palaeogeographic Evolution of Central Eastern Anatolian Basins, the Closure of the Neo-Tethys Ocean and Continental Collision

Abstract: In central eastern Anatolia which is located between Eurasia and Africa, the study of basin developments between late Eocene and early Miocene is of great importance for understanding the process of the closure of the Neo-Tethys Ocean and the formation of strike-slip faults and regional uplift. To study these, three basins were selected: the Sivas-Erzincan, Gürün-Akkisla-Divrigi (GAD), and Malatya basins. The study proposes that the opening of the GAD basin played a key role in the formation of the Ecemis faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
1
5
0
1
Order By: Relevance
“…Similarly, Topuz et al (2019) suggested that the Early Miocene represents probably a time of continental extension and exhumation in Eastern Anatolia and NW Iran. However, recent studies (e.g., Karadenizli et al, 2016;Gülyüz et al, 2020) confirm the Miocene time of collision between Eurasian and Arabian plates, which are also consistent with the proposed model of Okay et al (2010) and Cavazza et al (2018).…”
Section: Geodynamic Interpretationsupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly, Topuz et al (2019) suggested that the Early Miocene represents probably a time of continental extension and exhumation in Eastern Anatolia and NW Iran. However, recent studies (e.g., Karadenizli et al, 2016;Gülyüz et al, 2020) confirm the Miocene time of collision between Eurasian and Arabian plates, which are also consistent with the proposed model of Okay et al (2010) and Cavazza et al (2018).…”
Section: Geodynamic Interpretationsupporting
confidence: 83%
“…The timing of the initiation of continental collision between the Arabian and Eurasian plates is still debated. Contrary to the view of Early to Middle Miocene (Okay et al, 2010;Karadenizli et al, 2016;Açlan and Altun, 2018;Gülyüz et al, 2020) and Middle Miocene periods (Cavazza et al, 2018) for the onset of collision, van Hunen andAllen (2011), McQuarrie andvan Hinsbergen (2013) and Koshnaw et al (2017) advocated that by Middle Oligocene (~ 26 -Ma), Neo-Tethys oceanic crust had been consumed, and the Arabia-Eurasia continentcontinent collision initiated. On the other hand, for the Caucasus-Iran-Anatolia (CIA) collisional zone volcanism, Lin et al (2020), proposed a double subduction scenario (e.g., Skobeltsyn et al, 2014) and double slab break-off model (Erzurum-Kars Suture Zone in Pontide at North, Bitlis-Zagros Suture Zone in SE Anatolia at South), and suggested that break-off events occurred at ≈ 17 Ma (Early Miocene) at South (Bitlis-Zagros Suture Zone) and ≈ 9 Ma at North (Erzurum-Kars Suture Zone).…”
Section: Geodynamic Interpretationmentioning
confidence: 94%
See 1 more Smart Citation
“…The suture zone is marked by an ophiolitic belt that extends all along the southern margin of the Sakarya block and Pontid belt, which are parts of the Eurasian continent. Consecutive to this collision, a large marine foreland depression formed south of this suture zone during the Paleogene, and this depression became fragmented during the late Paleogene and Neogene under the neotectonic regime to form the main Central Anatolian basins—from west to east Beypazarı, Haymana-Polatlı, Tuzgölü, Çankırı, and Sivas basins (Görür et al, 1998; Görür and Tüysüz, 2001; Huvaz, 2009; Karadenizli et al, 2016; Poisson et al, 2016).…”
Section: Geologic Settingmentioning
confidence: 99%
“…6a) in the sequence representing dynamic sedimentation under high energetic conditions most likely controlled by regional tectonics that caused relief changes in the surrounding topography. Earlier activity on the Ecemiş Fault of the Central Anatolian Fault Zone was proposed as the end of early Miocene by some researchers (e.g., Karadenizli et al 2016) that coincide with this period. The available middle Miocene mammal fauna are represented by small forms (i.e., Rodentia, Insectivora and Lagomorpha; Fig.…”
Section: Middle Miocenementioning
confidence: 97%